Digitalisasi Pendidikan di Indonesia: Studi Penggunaan Moodle Elsmansa di SMAN 1 Purbalingga Jawa Tengah - Ihda Agustio Devanda Nurico Kamala; Hariyadi; Arizal Mutahir (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The main problem faced is the desire to use Moodle Elsmansa after the Covid-19 pandemic at SMAN 1 Purbalingga, especially related to technology adaptation and technical constraints. The pandemic accelerated the implementation of digital-based learning, including through a digital learning system using an e-learning platform. This study aims to explore the use of this e-learning platform in learning. This effort was made to overcome the obstacles and the success of the integration of Moodle Elsmansa as part of the digital education transformation. The research method used is a qualitative method. Data collection methods through observation, interviews and documentation. The results of the study show that Moodle Elsmansa is a platform that supports the convenience of digital-based learning that is relevant to date.